2012
DOI: 10.1016/j.ceca.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic organelles shape calcium signals and exo–endocytotic responses of chromaffin cells

Abstract: a b s t r a c tfluxes between the different cell compartments support the proposal that the chromaffin cell has developed functional calcium tetrads formed by calcium channels, cytosolic calcium buffers, the endoplasmic reticulum, and mitochondria nearby the exocytotic plasmalemmal sites. These tetrads shape the Ca 2+ transients occurring during cell activation to regulate early and late steps of exocytosis, and the ensuing endocytotic responses. The different patterns of catecholamine secretion in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 222 publications
(296 reference statements)
0
10
0
1
Order By: Relevance
“…In this context, we found that chromaffin cells contain two subpopulations of mitochondria that buffer the [Ca 2ϩ ] c transients with quite different capacities: population M1 takes up high Ca 2ϩ concentrations at subplasmalemmal sites while population M2 located at inner cytosolic sites takes up much lesser amounts of Ca 2ϩ (47). The relative contribution of these two mitochondrial pools and/or an altered mitochondrial Ca 2ϩ cycling through their uniporter and their Na 2ϩ /Ca 2ϩ exchanger (26) could explain the paradox of enhanced K ϩ -stimulated [Ca 2ϩ ] c transients with normal secretion in the mSOD1 with respect WT chromaffin cells.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, we found that chromaffin cells contain two subpopulations of mitochondria that buffer the [Ca 2ϩ ] c transients with quite different capacities: population M1 takes up high Ca 2ϩ concentrations at subplasmalemmal sites while population M2 located at inner cytosolic sites takes up much lesser amounts of Ca 2ϩ (47). The relative contribution of these two mitochondrial pools and/or an altered mitochondrial Ca 2ϩ cycling through their uniporter and their Na 2ϩ /Ca 2ϩ exchanger (26) could explain the paradox of enhanced K ϩ -stimulated [Ca 2ϩ ] c transients with normal secretion in the mSOD1 with respect WT chromaffin cells.…”
Section: Discussionmentioning
confidence: 96%
“…The secretory process in these cells involves granule transport, the translocation of the secretory vesicles to the plasma membrane, their docking at secretory sites and finally, the fusion of the vesicle with the plasma membrane that results in the extrusion of their soluble contents (Burgoyne et al, 1993). Distinct cellular structures play fundamental roles in different stages of this secretory cascade, such as the cortical cytoskeleton (Trifaro et al, 2008; Gutierrez, 2012; Meunier and Gutierrez, 2016; Villanueva et al, 2016), while organelles like the mitochondria and endoplasmic reticulum appear to control and shape the elevations in intracellular calcium that govern multiple steps of this cascade (Garcia-Sancho and Verkhratsky, 2008; Garcia et al, 2012; Garcia-Sancho et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Chromaffin cells (CCs) from the adrenal medulla have served as invaluable neurosecretory models for investigating the fine tuning of Ca 2+ signalling and exocytosis at molecular, cellular, physiological and pharmacological levels (Livett ; Neher ; Garcia et al . , ; Mahapatra et al . ).…”
mentioning
confidence: 99%
“…Chromaffin cells (CCs) from the adrenal medulla have served as invaluable neurosecretory models for investigating the fine tuning of Ca 2+ signalling and exocytosis at molecular, cellular, physiological and pharmacological levels (Livett 1984;Neher 1998;Garcia et al 2006Garcia et al , 2012Mahapatra et al 2012). These cells offer important advantages as they have compact cell bodies ideally suited for capacitance measurements, are accessible to amperometric electrodes and are readily loaded with Ca 2+ indicator dyes and caged Ca 2+ compounds.…”
mentioning
confidence: 99%